2018
DOI: 10.1111/ajo.12777
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of routine antenatal depression screening and psychosocial assessment in a regional private maternity setting in Australia

Abstract: This study highlights the need for, and acceptability of, depression and psychosocial assessment in the private maternity sector. These findings are particularly timely given the provision of new Medicare Benefits Scheme items for obstetricians to undertake psychosocial assessment (both antenatally and postnally) in line with recommended clinical best practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 18 publications
2
37
0
1
Order By: Relevance
“…However, the qualitative design of the study and the inclusion of a range of healthcare professionals ensured that the critical role they play in providing holistic health care to women in a regional area was both recognised and respected . Women’s perspectives were not explored within this study; however, their comfort and acceptability of the program have been previously reported …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the qualitative design of the study and the inclusion of a range of healthcare professionals ensured that the critical role they play in providing holistic health care to women in a regional area was both recognised and respected . Women’s perspectives were not explored within this study; however, their comfort and acceptability of the program have been previously reported …”
Section: Discussionmentioning
confidence: 99%
“…An integrated psychosocial model of care, comprising routine administration of the Antenatal Risk Questionnaire (ANRQ) and Edinburgh Postnatal Depression Scale (EPDS) at a woman’s first antenatal booking visit, was introduced at the participating site in April 2015, and included localised protocols for referral for additional assessment or support as required. This program has achieved a participation rate of nearly 90% …”
Section: Methodsmentioning
confidence: 99%
“…Based on the increasing international move to standardise as routine the psychosocial assessment and depression screening of all pregnant women and offer relevant support [40][41][42], different options need to be considered in order to enhance psychosocial care. Some of the interventions that are applied in certain countries globally are reflected in Table 2.…”
Section: Qualitative Findingsmentioning
confidence: 99%
“…Two studies of private hospitals that had implemented an assessment program demonstrated high levels of acceptability [19,26]. One of the focus group participants explained that as women are under the care of an obstetrician prenatally the midwives may be restricted in the assessment they can conduct.…”
Section: Part Of Routine Carementioning
confidence: 99%
“…The comprehensive assessment of risk of mental illness as part of routine, coordinated perinatal care has been demonstrated to be feasible and highly acceptable in the private hospital setting [26,43] and should be available to all women who give birth in a private hospital.…”
Section: Recommendationsmentioning
confidence: 99%